Knowledge of and attitudes towards erosive tooth wear among students of two Chinese universities - Deng-wei Hong; Xiu-jiao Lin; Annette Wiegand; Hao Yu (BMC, 2020)
Abstract Background To assess the knowledge of and attitudes towards erosive tooth wear among dental, medical, and non-medical university students of two Chinese universities. Methods A questionnaire containing 15 questions on knowledge of erosive tooth wear and 10 questions on attitudes towards erosive tooth wear was designed, and its psychometric properties (reliability and validity) were analysed in a pilot study (n = 120 students). The following 3 groups of university students (n = 635) were recruited based on a convenience sampling technique and were distributed the questionnaire via an online survey system: dental students (DSs), medical students (MSs), and non-medical students (NSs). Differences in the scores between groups and genders were analysed by one-way analysis of variance (ANOVA). The Pearson correlation coefficient was used to determine the association between the knowledge and attitude scores (P < 0.05). Results The questionnaire was found to be reliable, valid and reproducible. A total of 435 students participated in this study (response rate: 69.6%). The knowledge score of the DSs (11.5 ± 3.4) was significantly higher than those of the NSs (5.5 ± 4.0) and MSs (6.1 ± 4.0) (P < 0.001). The attitude score of the DSs (45.2 ± 6.5) was significantly higher than those of the NSs (41.1 ± 6.9) and MSs (41.8 ± 6.4) (P < 0.001). The majority of DSs expressed attitudes that were more accurate and positive than those expressed by the other 2 groups. The attitude score was positively correlated with the knowledge score (r = 0.237, P < 0.001). Conclusions Dental students had more accurate knowledge of and more positive attitudes towards erosive tooth wear than medical and non-medical students. In this population, a positive correlation was established between knowledge of and attitudes towards erosive tooth wear.